Study on fatty acids composition of Pinna nobilis species collected in the coastal areas of Phan Rang Bay and South Binh Thuan, Vietnam - Dang , Thi Phuong Ly; Dao, Thi Kim Dung; Nguyen, Thi Nga; Dang, Thi Minh Tuyet; Ngo, Thu Trang; Trinh, Thi Thu Huong; Luu, Tuan Anh; Grigorchuk, Valeriia Petrovna; Pham, Quoc Long (Vietnam Journal of Marine Science and Technology, 2026)
The fatty acid composition of Pinna nobilis samples collected from Phan Rang Bay and South Binh Thuan, Vietnam, was investigated. A total of 40 fatty acids, with chain lengths ranging from C14 to C24, were identified across the samples. The fatty acid profiles exhibited notable diversity, comprising saturated fatty acids (SFAs), branched-chain saturated fatty acids, monounsaturated fatty acids (MUFAs), and polyunsaturated fatty acids (PUFAs). SFAs accounted for 39.09% of the total fatty acids in the P. nobilis sample from Phan Rang Bay, compared to only 7.50% in the South Binh Thuan sample. The MUFA contents were 7.95% and 13.58%, respectively. Notably, the PUFA content was markedly higher in the South Binh Thuan sample (77.48%) than in the Phan Rang Bay sample (43.73%). The predominant fatty acids included 16:0, 18:1n-7, 18:1n-9, 16:1n-9, eicosapentaenoic acid (EPA, 20:5n-3), docosahexaenoic acid (DHA, 22:6n-3), and arachidonic acid (AA, 20:4n-6). Among these, DHA was the most abundant fatty acid in both samples, representing 16.39% and 29.30%, respectively. The total omega-3 (n-3) fatty acid content ranged from 22.89% to 51.07%, while the omega-6 (n-6) fatty acid content ranged from 20.84% to 26.41%, yielding favorable n-3/n-6 ratios of 1.10 and 1.93. These findings indicate that P. nobilis from these regions is a highly nutritious marine resource rich in essential fatty acids with an optimal n-3/n-6 ratio. Consequently, it holds significant economic value and high potential for future commercial exploitation and functional food development.